Penyebab Kehadiran Calon Tunggal Dalam Pemilihan Kepala Daerah - Ayu Lestari (Universitas Sriwijaya, 2018)
Indonesia is one of the countries that embrace the democratic system in running the goverment. One manifrstation of democracy is the General Election (GE). In the end, people’s power apparently still has a large role in the General Election. This can be seen from the regional head election that took place in the city of Makassar. The people of Makassar preferred empty boxes rather than the sole candidate supported by political parties. This research discusses the juridical review of the victory of the empty box in the Regional Head General Election. This is a normative study with the types and sources of legal material taken from secondary data. The legal materials were gathered through literature review and analyzed qualitatively with deductive conclusions.The results of the study showed that the factors of sole candidates in the regional head elections were divided into juridical factors and non-juridical factors. Juridical factors started with the decision of the Constitutional Court Number 100 / PUU-XIII / 2015. Non-juridical factors are as follows: the nominating process requires high costs and the existence of money politics; weak competitiveness of candidates in political competition; the political interests of the political elite; and the failure of political parties to give political education to cadres. The legal consequence of winning an empty box against a sole candidate is that if the sole candidate loses a valid vote gain of less that 50%, then the next election will be held again in the following year